In Silico Modeling of the Immune System: Cellular and Molecular Scale Approaches. (6th April 2014) - Belfiore, Mariagrazia; Pennisi, Marzio; Aricò, Giuseppina; Ronsisvalle, Simone; Pappalardo, Francesco
Abstract : The revolutions in biotechnology and information technology have produced clinical data, which complement biological data. These data enable detailed descriptions of various healthy and diseased states and responses to therapies. For the investigation of the physiology and pathology of the immune responses, computer and mathematical models have been used in the last decades, enabling the representation of biological processes. In this modeling effort, a major issue is represented by the communication between models that work at cellular and molecular level, that is, multiscale representation. Here we sketch some attempts to model immune system dynamics at both levels.